FROM "PROSVITA" SOCIETY HISTORY OF POBEREZHIA VILLAGE - Лончина, Г. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article reproduces the pages of the "Prosvita" society in the Poberezhia village based on the memories of its inhabitants. The appendix contains abstracts of books from the library of the society saved by Myron Leshyshyn.